An Information System Study on the Billing and Collection System of Luzon Integrated Services, Inc. - Advincula, Ophelia; Ablan, Evelyn; Autajay, Alan; Bucsit, Angelina; Ludovice, Lyna (College of Engineering, 1986)
There are a lot of reasons why the group did a study on the Billing and Collection System of Luzon Integrated Services, Inc. (LINSI). First and foremost, an Information System study is one of the requirements of IE 54. Secondly, due to time constraint, we had to limit ourselves to a relatively smaller system as well as one where we knew the right persons and where we can gather the required data. Thirdly, the group wants to assist management in analyzing the current Information System and provide a structure for documenting, describing and analyzing the Billing and Collection System of LINSI. Lastly, the group hopes that this study would be beneficial to the company not only to the studied system but to LINSI as a whole.